(untitled) (Journal of Civil Engineering Researchers, 2023)
Fiber self-compacting concrete (FSCC), is a concrete that has been combined with fiber in its mix design. Extensive benefits of self-compacting concrete (SCC) in full fill the mold and achieving full compaction without vibration, with good behavior after concrete cracking, raise the idea of self-compacting concrete production. The fundamental challenge in this area is the unsatisfactory performance of concrete with fibers; In other words, using fibers in concrete will reduce concrete fluidity. Therefore, determining the appropriate percentage of fibers in SCC can be a precursor to extending the use of FSCC. In this study, polypropylene fibers with 0.5, 1, 0.1, and 2% of concrete mix design have been added to the self-compacting concrete mix design. Its impact on the performance of concrete has been evaluated using time and diameter of slump-flow, L-Box, J-ring, and V-funnel flow time tests. Based on the criteria defined by EFNARC standard, it was indicated that the FSCC containing 0.5% polypropylene fibers has an acceptable performance. Additionally, the effect of polypropylene fiber on the mechanical properties of hardened concrete has been studied using compressive strength and tensile tests and shown that changes in FSCC compressive strength and tensile with 0.5% polypropylene fiber are negligible.